2013
DOI: 10.1007/s00417-013-2497-y
|View full text |Cite
|
Sign up to set email alerts
|

Macular buckling for previously untreated and recurrent retinal detachment due to high myopic macular hole: a 12-month comparative study

Abstract: Macular buckling combined with PPV should be considered a preferred surgical approach both in primary and recurrent retinal detachment secondary to MH in high myopic eyes. Nevertheless, visual outcomes seem to be better when macular buckling is chosen as first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Different techniques have been used together with modern vitrectomy techniques [50][51][52]. Pars plana vitrectomy is useful for removing two of the main tractions that cause myopic traction maculopathy: vitreous traction and an abnormally rigid ILM.…”
Section: Macular Buckling?mentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques have been used together with modern vitrectomy techniques [50][51][52]. Pars plana vitrectomy is useful for removing two of the main tractions that cause myopic traction maculopathy: vitreous traction and an abnormally rigid ILM.…”
Section: Macular Buckling?mentioning
confidence: 99%
“…MH closure in eyes with high axial length is difficult to obtain by vitrectomy alone due to the disproportion between the retina and the pronounced staphyloma [42]. Alkabes et al [52] obtained excellent anatomic and visual outcomes in the treatment of MHRD with macular buckling. Though the results were positive in previously vitrectomized eyes as well as untreated eyes, the results were superior when macular buckling was the first-choice technique.…”
Section: Macular Buckling?mentioning
confidence: 99%
“…Clinically, HM is often associated with low best-corrected visual acuity (VA). Besides, HM may lead to macular complications,6 chorioretinal atrophy,7 and retinal detachment 8. Currently, the important methods for HM correction include among other excimer laser9 and orthokeratology 10…”
Section: Introductionmentioning
confidence: 99%
“…In the comparative study of Ripandelli et al ,14 four of 15 patients who underwent PPV for MHRD had a retinal re-detachment because of a persistent MH, and were successfully treated with additional MB. In another recent study, Alkabes and Burés-Jelstrup et al 43 demonstrated that MB combined with PPV should be considered a preferred surgical approach both in primary and recurrent RD secondary to MH in high myopic eyes.…”
Section: Discussionmentioning
confidence: 99%